SYNTHESIS AND STUDY OF THE PHOTOCHROMIC BEHAVIOR OF SUBSTITUTED 6'-NITRO-1,3,3-TRIMETHYL-5-VINYLSPIRO(INDOLINO-2,2'-[2H]CHROMENES) - A. V. Laptev; A. Yu. Lukin; N. V. Belikov; O. V. Demina; S. D. Varfolomeev; V. A. Barachevsky; A. A. Khodonov; V. I. Shvets (Тонкие химические технологии, 2013)
Few 5-vinyl substituted 6’-nitro-1,3,3-trimethylspiro(indolino-2,2’-[2H]chromenes) (6’-nitro-spiropyrans) were synthesized by a one-step method from 5-formyl precursor – 5-formyl-6’-nitro-1,3,3-trimethylspiro(indolino-2,2’- [2H]chromene) (1). 5-Vinyl-6’-nitro-spiropyran (2) was prepared by the Wittig olefination of 1 with an ylide, which was generated by the action of potassium tert-butylate on methyltriphenylphosphonium bromide in THF. E-6’- Nitro-5-(1’’-nitroethene-2’’-yl)-6’-nitro-spiropyran (3) was obtained by heating 1, nitromethane, ethylenediammonium diacetate at 50°С in absolute methanol and inert atmosphere. Compounds 1’’-[6’-nitro-spiropyran-5- yl]-2’’,2’’-dicyanoethylene (4) and E-1’’-[6’-nitro-spiropyran-5-yl]-2’’-cyano-2’’-methoxycarbonylethylene (5) were prepared from initial 1 by reflux in ammonium acetate / glacial acetic acid / benzene mixture with malonodinitrile or methyl 2-cyanoacetate, respectively. The procedure for synthesizing derivatives 2’’,2’’-dimethyl-5’’-(6’-nitrospiropyran-5-yl)methylidene-1’’,3’’-dioxane-4’’,6’’-dion (6) and 5’’,5’’-dimethyl-2’’-(6’-nitro-spiropyran-5-yl)- methylidenecyclohexane-1’’,3’’-dion (7) includes the interaction of Meldrum's acid or dimedone, accordingly, with 5-formyl precursor 1 by heating in ethanol in the presence of piperidine and molecular sieves (to bind the released water). The structures of the prepared compounds and their purity have been confirmed by physico-chemical analysis. A spectral kinetic study of the photochromic properties of the substituted 5-vinyl spiropyrans was carried out in toluene and ethanol solutions. The 5-vinyl-6’-nitro-spiropyran derivatives 2–7 described in this work are of interest for further synthetic transformations.